Explanation of entrepreneurship small business challenges in rural area, The case of study: Bijar, Iran - Hossein Farahani; Mina Alvandi (تحقیقات کاربردی علوم جغرافیایی)
The migration of young people and the aging of rural communities, for reasons such as poverty and unemployment, will create a lot of need for identifying new approaches to the survival of rural communities. Small business entrepreneurship has an important role in reducing poverty and, ultimately, rural development. However, this kind of entrepreneurship faces many challenges in terms of environmental, economic and ... The purpose of this research is to examine the challenges of entrepreneurship in improving entrepreneurship, creating employment and sustainable income through setting up small businesses. The present research is aimed at applying the field of observation and control, and in terms of the nature and method of descriptive-analytical. The statistical population of the study consisted of rural households living in Bijar. According to the census of 1395, the population of this city was 89,162 persons, which according to the distribution of 44% of the rural population and 56% of the city. There are also 283 rural villages in the seaside district, among which 12 villages have entrepreneurship and 244 of them are households using the modified Cochran formula. Data gathering method was library and field questionnaire (questionnaire). In this questionnaire, individuals were asked to identify the importance of each of the identified challenges in rural small business based on the options of this spectrum (high, high, medium, low, and very low) based on the Likert spectrum. Structural Equation Modeling (Factor Analysis) has been used for analyzing data in Amos software. The results of the research show that all challenges in the entrepreneurship of small businesses have been affected, but economic factors with factor load of 0.91 have the highest impact among existing challenges and the individual and social challenges with factor load are 0.23 and 0.28, respectively. The least load has been the factor.